THE ROLE OF COUNSELING SERVICES IN EMPOWERING WOMEN'S MENTAL HEALTH - Liley Afzani Saidi; Nur Haffiza Rahaman; Wan Sue Emi Yusnita Wan Yusof; Siti Nurhafizah Saleeza Ramlee; Rayyan Cheong Tiang Ming Abdullah, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Women nowadays face various problems, especially in adjusting to new jobs and obligations. One of the consequences of adversity is mental health problems. As a result, one of the methods to help women's emotional support is to provide counseling services to increase their level of well-being. Therefore, the objectives of this study include: i) identifying the components of empowerment that are applied in the implementation of counseling sessions, especially those involving mental health handled by counselors; and ii) identifying mental health issues that counselors always handle when dealing with clients involving women. This study involves a qualitative technique, which is a single-case study conducted by interview with counselors who are trained and responsible for dealing with issues related to mental health and women. Interview findings will be classified using a verbatim approach, particularly those related to women's empowerment and therapies to improve mental health among women. The results of this study found that there are five sub-themes that are known for sure to empower mental health in the implementation of counseling sessions, which involve Perspective on Human Nature, Problem Clarification, Power Relationship between Client and Counselor, Power Analysis, and Skill Development. In addition, the results of the interview also show that counselors who conduct counseling sessions with female clients are always faced with issues related to depression, stress, problems at work, abuse, and relationship problems.